Usando o Scratch para potencializar o pensamento criativo em crianças do ensino fundamental - Martins, Amilton Rodrigo de Quadros (2012)
The present study aims to elucidate the potential use of computer programming environments in the development of creative thinking in students from elementary school. The intention was to seek subsidies for understanding of the potential of these environments in the development of creative thinking, based on autonomy, curiosity and leadership. The research uses theoretical background as the dialogue between action and experimentalist pragmatist John Dewey, the constructivist logic of Jean Piaget, the constructionist approach contratecnicista of Seymour Papert and modern application of these three concepts suggested by Mitchel Resnick MIT, offering a proposal methodology for technology transfer and application of these concepts in technology workshops addressed. This is a qualitative study of a trial conducted through workshops Scratch tool at the beginning of which techniques were used focus groups with young people, and subsequently offered to solve challenges using creativity and logic. The participants belong to a class of 6th grade of a public school participant of the study group. As a result, we tried to identify, analyze and talk about attitudes that demonstrate the use of categories of analysis that can highlight intentional use of creative thinking during the search. The workshop counted with six stages and, during its execution, the moments of experimentation were documented and analyzed from the perspective of